2013
DOI: 10.1002/cjoc.201300536
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Coupling Reactions of Pyrimidin‐2‐yl Sulfonates with Phenols and Anilines: An Efficient Approach to C2‐Functionalized Pyrimidines

Abstract: Pyrimidin‐2‐yl sulfonates, as an efficient reaction partner, which can be easily prepared from cheap commercial materials, were coupled with phenols and anilines to give a wide array of C2‐aryloxy‐ and arylaminopyrimidines in good to excellent yields under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…We have reported the synthesis of 2‐phenolic pyrimidines by C‐S and C‐O cross‐coupling reaction of pyrimidin‐2‐yl sulfonates with aryl thiols and phenols [12]. Alternatively, we have developed an efficient preparation of 2‐arylated pyrimidines by the Mitsunobu reaction between 2‐hydroxypyrimidine and phenols.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported the synthesis of 2‐phenolic pyrimidines by C‐S and C‐O cross‐coupling reaction of pyrimidin‐2‐yl sulfonates with aryl thiols and phenols [12]. Alternatively, we have developed an efficient preparation of 2‐arylated pyrimidines by the Mitsunobu reaction between 2‐hydroxypyrimidine and phenols.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our group has successfully achieved the synthesis of tetra‐substituted pyrimidine derivatives via diverse cross‐coupling reactions of pyrimidin‐2‐yl tosylates with arylboronic acids, terminal alkynes, Grignard reagents and O‐, S‐ and N‐nucleophiles (Scheme ). The tetra‐substituted pyrimidine derivatives usually have wide pharmacological applications, such as calcium channel modulators, α1a‐adrenergic agonists, mitotic kinesin inhibitors, antibacterial profiles, etc .…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological fight against cancer has made significant progress in the last twenty years. [4,5] Many papers have reported that pyrimidine derivatives showed impressive anticancer activity [6][7][8][9] and several members of this class have earned valued places in chemotherapy as effective agents, like 5-fluorouracil, tegafur, carmofur and fluoroadenosine. [1] Although many chemotherapeutic agents have been developed to treat different kinds of cancer effectively, some side effects could happen simultaneously.…”
Section: Introductionmentioning
confidence: 99%